Universidades federais de missão institucional internacional e seu papel para a política externa brasileira - Almeida, Felipe Cordeiro de (2022)
The thesis aims to present the role of universities with international institutional missions in Brazilian foreign policy in the 2010s. The Federal University of Latin American Integration (UNILA) and the Federal University of International Integration of Afro-Brazilian Lusophony (UNILAB) were created as educational institutions intended to fulfill international institutional missions in line with the foreign policy of the second government of President Luiz Inácio Lula da Silva, when they were idealized. Thus, the institutions came to compose the broad set of national policies aimed at the internationalization of higher education developed in the 2010s, as well as other initiatives such as the Science without Borders Program and the Institutional Program for Internationalization of the Coordination for the Improvement of Higher Education Personnel. Among this set of internationalization initiatives, universities stand out for having their creation and development founded on interests that overflow the notions of educational, scientific, cultural and economic development, with which the vast majority of other national internationalization policies can be explained. UNILA and UNILAB are also part of the Brazilian international cooperation for development, having a relevant role in the Brazilian insertion in the South-South international cooperation, following the example of traditional initiatives such as the Programa Estudanteconvênio Graduação. Thus, the institutional missions of universities aimed at Brazilian integration with regions prioritized by foreign policy in the historical context of their creation were the basis for their development during the following decade. This development can be characterized by movements towards and away from foreign policy throughout the decade, as the policy changed and UNILA and UNILAB matured as institutions towards their full constitutional autonomy. It is to this peculiar contribution that goes beyond the limits of traditional internationalization and development cooperation tools that this thesis is dedicated. The research is based on a vast bibliographic production in the fields of educational internationalization, international cooperation and foreign policy, and, as primary sources, official documents from universities, ministries, federal agencies and interviews conducted with UNILA technicians and managers